2021
DOI: 10.1055/a-1336-2371
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Tocilizumab for Coronavirus Disease 2019 (Covid-19) Patients: A Systematic Review and Meta-analysis

Abstract: Background Currently, the data regarding the effectiveness and safety of tocilizumab as treatment for COVID-19 infection is still conflicting. This study aims to give clear evidence regarding the potential benefit and safety of tocilizumab in improving the outcome of COVID-19 patients. Methods We systematically searched the PubMed and Europe PMC database using specific keywords related to our aims until November 1st, 2020. All articles published on COVID-19 and tocilizumab were retrieved. Statistical analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0
8

Year Published

2021
2021
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 50 publications
2
39
0
8
Order By: Relevance
“…The result of this review suggested the benefit of IL-6 inhibitors in reducing mortality rate based on an analysis of thirteen studies. This result is in line with several recent systematic reviews that reported a lower mortality rate in the tocilizumab group than the control group [ [38] , [39] , [40] , [41] ]. COVID-19 replication causing pyroptosis of the target cell, thus inducing synthesis of pro-inflammatory cytokine [ 28 ].…”
Section: Discussionsupporting
confidence: 91%
“…The result of this review suggested the benefit of IL-6 inhibitors in reducing mortality rate based on an analysis of thirteen studies. This result is in line with several recent systematic reviews that reported a lower mortality rate in the tocilizumab group than the control group [ [38] , [39] , [40] , [41] ]. COVID-19 replication causing pyroptosis of the target cell, thus inducing synthesis of pro-inflammatory cytokine [ 28 ].…”
Section: Discussionsupporting
confidence: 91%
“…Our results showed that tocilizumab treatment was associated with a lower risk of mortality, whereas were not effective for shortening time on the length of hospital stay or the time from illness onset to outcomes. In fact, consistent with our study, a meta-analysis 28 which included 38 studies reported that tocilizumab treatment is associated with a reduction of mortality from COVID-19, although tocilizumab treatment did not alter the severity of COVID-19 and the length of hospital stay. Similarly, a systematic review and meta-analysis on critically ill COVID-19 patients 16 showed tocilizumab to be efficacious in reducing mortality; moreover, another systemic review and meta-analysis also confirmed the effectiveness of tocilizumab treatment in reducing the risk of admission to ICU, use of ventilation and mortality 29 .…”
Section: Discussionsupporting
confidence: 92%
“…Based on our meta-analysis we found correlation between weather on the COVID-19. Temperature and humidity are most crucial weather factors that are string enough to impact over the death rate and incidence of COVID-19 42 , 43 . All the articles included into this study adhere to the weather centric approaches to the COVID-19.…”
Section: Discussionmentioning
confidence: 99%